Front cover illustration - "They passed on" (International Library of African Music, 1965)
The cover illustration for this edition of the Journal is taken from 'Tbe Zambezi and its Tributaries’ by David and Charles Livingstone, published in 1865 by John Murray, Albemarle Street, London. The caption to the engraving is Women with water-pots listening to the music of tbe Marimba, Sansa and Pan's Pipes.
Keywords: African Music